The light at the bottom of the world - Shah, London (Shah, London. Light at the bottom of the world, 2019)
Teenaged Leyla McQueen, who lives beneath the ruins of a submerged London in 2099, joins a prestigious submersible race in the hope of clearing her father's name before encountering government corruption and a hidden world.